Creativity Development Oriented Poetry Text Learning Model - Fatah, Deni Abdul; Jaja Wilsa; Mascita, Dede Endang (International Journal of Educational Research Excellence (IJERE), 2025)
This research aims to: (1) produce a discovery learning model that can develop the creativity of SMP/MT students in learning poetry texts and (2) determine valid and practical criteria for the discovery learning model being developed. This study uses research and development methods with the ADDIE model (analysis, design, development, implementation, and evaluation). The steps of this research consisted of needs analysis, learning model design, learning model development, product implementation, and product evaluation. Data were collected through interviews, questionnaires, expert validation,z and student assessment. The data obtained were descriptively analyzed using a Likert scale. The research results obtained are as follows: (1) The product developed in this research is the Discovery Learning model using picture sketches that can develop the creativity of SMP/MT students in learning poetry texts. (2) The learning model development is classified as "Valid" with an assessment of 80%, the RPP is in the "Very Valid" category with a result of 91.2%, the LKS is in the "Very Valid" category with a result assessment of 83.92%, and the Learning Outcomes Test is in the category "Very Valid" with an assessment result of 92.77%. (3) The development of this learning model meets the practical need of teachers with an assessment of 84.23%. In addition  , based on the results of teacher observations during the implementation process, 19 of the 21 planned activities were  implemented by teachers and students. (4) Based on the paired sample test, the Sig value is known. (2-tailed) is 0.000 < 0.005, so it can be concluded that there is an average difference between the post-test and pre-test results, which means that there is an influence of the sketch drawing learning model on students' learning abilities. develops students' creativity in school.